1973
DOI: 10.1002/j.1537-2197.1973.tb05949.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin‐gibberellin Regulation of Shoot Development and Leaf Form in Tobacco Plantlets

Abstract: Callus and plantlets derived from callus cultures of Nicotiana tabacum var. Wisc. #38 were grown on medium containing serial combinations of gibberellic acid (GA3) and the cytokinin 6‐(3‐methyl‐2‐butenylamino)purine (2iP). Increasing levels of both growth substances resulted in the production of greater amounts of both callus and shoot tissue. More buds were induced when the cytokinin level was increased, and this effect was counteracted by raising the GA3/2iP ratio. Furthermore, the size and form of the shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Here we identify positive regulation of GA as one way by which LA‐like factors promote differentiation. GA is known to promote tissue expansion and differentiation (Engelke et al. , 1973; Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Here we identify positive regulation of GA as one way by which LA‐like factors promote differentiation. GA is known to promote tissue expansion and differentiation (Engelke et al. , 1973; Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous gibberellin levels are correlated with leaf size and shape in pea ( Ross, Murfet & Reid 1993) and tomato ( Nagel 1998). Exogenous cytokinin and gibberellin both stimulate cell expansion ( Engelke, Hamzi & Skoog 1973), but neither acts via an ‘acid‐growth’ mechanism in bean leaves ( Brock & Cleland 1989). Abscisic acid inhibits leaf expansion, perhaps by interacting with potassium conductance and interfering with proton efflux ( Van Volkenburgh & Davies 1983; Bacon, Wilkinson & Davies 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In summarizing the early auxin investigations, these authors also concluded that all of the available data "fit in with the view that auxin causes elongation of leaf veins, while the growth of the mesophyll depends on other factors" (Went and Thimman, 1937). This idea that leaf development is controlled by chemically distinct vein growth factors or "caulocaline" and mesophyll growth factors or "phyllocaline" (Went, 1951) was supported by the observation that treatment with adenine (Bonner and Haagen-Smit, 1939) and cytokinins (Engelke et al, 1973) promoted mesophyll growth but not veinal growth. …”
mentioning
confidence: 98%